Critical reading in English as a second language - Muhamad, Ainon Jariah; Mohd. Asraf, Ratnawati (2007)
The purpose of this study was to examine whether tertiary level students were able to respond critically to English academic texts. Examining the extent to which critical reading strategies are used will give an insight into the reading process, a useful feedback in the teaching of reading. Based on the premise that critical thinking is an important educational objective, and that tertiary level reading is an interactive process involving higher order skills, it is only fitting to look into the critical reading process, specifically at the strategies the students adopt in their attempts at constructing meaning. For the purpose of this study, the critical reading strategies are defined based on the critical thinking skills model by Facione (2004). The think aloud data constituted the main source of data on the reading strategies. Findings revealed that although the students were able to utilize the critical reading strategies, they were only able to do so to a certain extent. It is also an indication that there is still a lot to be done to improve students’ ability to think and read critically, and should be reflected in the curriculum, especially when English is used as the medium of tertiary level instruction.